Evaluation of flavonoid composition and biological activities of hydrolyzed whole pomelo juice - Xie, Xi; Zhuang, Shanshan; Gu, Yanxia; Shen, Yunrui; Zhang, Weisi; Ma, Lukai; Xiao, Gengsheng; Wang, Qin; Zhong, Yonghui; Liu, Huifan (Frontiers in Nutrition, 2026)
This study aimed to investigate the bioactive compounds and evaluate the antioxidant and anti-inflammatory properties of juice prepared from whole pomelo fruits (WPJ). Methods: Total flavonoid content, naringin levels, and nutrient composition of WPJ were quantified over the storage period. Flavonoid profiling was conducted using LC–MS. Anti-inflammatory activity was assessed in vitro using LPS-stimulated RAW264.7 macrophages, where dose–response effects on nitric oxide (NO), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) were measured. An in vivo phenol red–induced mouse model was used to evaluate the effects of WPJ on respiratory secretion and pulmonary inflammation, with analysis of MAPK/NF-κB signaling pathways. Results: WPJ exhibited a high total flavonoid content (950.68 ± 7.65 mg/100 g), dominated by hesperidin, tribuloside, baicalin, apigenin 7-O-neohesperidoside, hesperetin, neohesperidin dihydrochalcone, naringenin, naringin, jaceosidin, and pinocembrin. In vitro, WPJ pretreatment significantly reduced NO, IL-6, and TNF-α production in LPS-stimulated RAW264.7 cells in a dose-dependent manner. In vivo, WPJ promoted phenol red secretion in the respiratory tract and attenuated pulmonary inflammatory responses, partly through inhibition of MAPK/NF-κB signaling. Conclusion: The results demonstrate that WPJ is rich in diverse flavonoids and possesses potent anti-inflammatory activity both in vitro and in vivo. Its ability to suppress key inflammatory mediators and modulate respiratory tract responses suggests potential benefits for pulmonary health. These findings support the potential application of WPJ as a functional food for preventing or alleviating cough- and phlegm-related conditions.